Mentor-Mentee Experiences Amidst COVID-19: A Teaching Practice Case Study - Cias T. Tsotetsi; Selloane A. Mile (Research in Social Sciences and Technology- OpenED Network, 2021)
Preparing student teachers for the world of work is seen globally as a challenge. This research aims to explore mentors and mentees experiences in teaching practice during the COVID-19 period. In order to explore the challenge in this study, the following research question guided the paper: What are the teaching practice experiences of mentors and mentees at a school during COVID-19? The research question is a result of limited research done on the experiences of two groups during COVID-19. Informed by the realist social theory, we generated data via telephonic interviews with mentors and mentees in one school. The data was generated through semi-structured Interviews and thematic analysis was a method employed in the analysis of the data. The results present challenges experienced by mentees which, amongst others, include a feeling of inadequacy or a lack of confidence in their abilities to bring about order to the classroom and a feeling of being excluded in meetings and extra-curricular activities. On the other hand, mentors receive mentees without any prior warning or without arrangements made to accommodate them and the absence of the university officials except for assessment. Based on the results, a collaborative approach should be employed to deal with some of the challenges experienced by mentors and mentees.